British economic regulators in an age of politicisation: from the responsible to the responsive regulatory state?. Issue 11 (1st November 2020) - Koop, Christel; Lodge, Martin
ABSTRACT: The regulatory state that developed in Britain and elsewhere in the 1980s and 1990s was characterised by independent agencies, efficiency-based objectives, 'econocratic' analysis, and an emphasis on output- and outcome-based legitimacy. Yet, with economic regulation becoming increasingly politicised, the 'responsible' regulatory state has come under pressure. How have British regulators adapted to these changes? Building primarily on interviews with regulators, we find that the regulatory state has become more responsive to broader political and public concerns. Key responsible features have been maintained, but new responsive layers have been added, contributing to a broadening of decision-making and conceptions of regulation, a greater role for communication and outward-oriented activities, and a widening of stakeholder engagement and accountability. Though supporting theories of organisational reputation and survival, the (ongoing) changes raise new questions about how much 'political space' independent economic regulators can feasibly and legitimately occupy.